Severe chronic abuse of zolpidem for over 10 years: a case report and review of similar cases - Moshfeghinia, Reza; Jazi, Kimia; Kabaranzadghadim, Shabnam; Malekpour, Mahdi; Oji, Bahare (Frontiers in Psychiatry, 2023)
Background: Insomnia is a major health issue and zolpidem is an effective treatment for insomnia. However, high doses of zolpidem can cause dependence, abuse, and withdrawal symptoms, questioning its advantages.Case presentation: A 39-year-old woman who has been divorced and unemployed for two years was referred to an addiction treatment center with a chief complaint of "seizure-like withdrawal symptoms after consuming high doses of zolpidem (up to 6000 mg per day) for a decade". These symptoms were in the form of body tremors, nystagmus, stress, anxiety, hot flashes, and sweaty palms. She has been undergoing detoxification by clonazepam for almost 2 months. Except for the first few days, she did not have any withdrawal symptoms, and her insomnia caused by zolpidem has improved.Conclusions: Chronic abuse of zolpidem can cause dependence, withdrawal symptoms, and abuse. High doses can lead to extreme craving and dependence. Physicians must manage the withdrawal process.